Incidence of norovirus in tropical seafood harbouring fecal indicator bacteria. (January 2020) - Das, Oishi; Lekshmi, Manjusha; Kumar, Sanath; Nayak, Binaya Bhusan
Abstract: The occurrence of human norovirus (HuNoV) in fresh seafood was studied by reverse transcription-polymerase chain reaction (RT-PCR). Samples ( n = 104) comprising of oysters, clams, shrimps and finfish were collected from 3 retail markets, a landing center and a rocky intertidal zone. The samples were subjected to virus concentration, followed by RNA extraction and RT-PCR. Of these, 43 (41.34%) samples were positive for HuNoV Group II (GII). The fecal contamination status of the samples was determined by the Most Probable Number (MPN) method. All (100%) the samples were fecally contaminated, with the fecal coliform counts ranging from 10 to >1400 MPN/100 g. The study shows that fresh seafood, especially the bivalve mollusks, can act as vehicles for transmission and spread of HuNoV in the community. The high level of HuNoV contamination of seafood not only constitutes a health risk to the domestic consumers, but also compromises the microbiological qualities of seafood meant for international trade. Graphical abstract: Unlabelled Image Highlights: Seafood samples were analysed for HuNoV by reverse transcription PCR Norovirus Group II (GII) was detected in 41.34% of the samples contaminated with fecal indicator bacteria The highest incidence of HuNoV was in bivalve molluscs (52.7%), followed by finfish (16.7%) and crustaceans (11%). High occurrence of HuNoV highlights the problem of widespread anthropogenic contamination of coastal ecosystem